Violent Non-State Actors in World Politics - Edited By Klejda Mulaj (London Hurst & Company, 2010)
The 2008 attacks on Mumbai were carried out by a Pakistani militant group known as Lashkar i-Taiba, termed a 'non-state actor' by Pakistan's president, Asif Zardari. In most cases, violent non-state actors (VNSAs) rise as a state fails, resorting to organized attacks as a brutally effective method for advancing their political aims and other goals. Currently operating in Afghanistan, Lebanon, Somalia, and Sudan, VNSAs can take the form of national liberation movements confronting an occupying force; insurgents engaged in protracted political and military struggles that eat at the power and legitimacy of a ruling government; terrorists who use threats or violent acts to effect political change; irregular yet recognizable armed forces working within an ungoverned area or failing state; and mercenary militias, such as those used by Shell, or army-loaded units, such as those used in the Niger Delta. The essays in this volume map the relationship between VNSAs and the state, following the political, economic, and social processes that contribute to the emergence of these groups and how VNSAs in turn use these processes to trigger a crisis of the state. Contributors locate the point in which violence becomes desirable to the non-state actor and whether this alters the purpose of the relationship between VNSAs and the state, and they track the influence that the former can have in reshaping the governments they tear down. One of the first resources to describe these groups in full, this volume explains the internal structure of VNSAs, their recruitment strategies and leading ideologies, the characteristics and partnerships that allow them to adapt and prosper, and the fundamental similarities and differences between groups.
Include Index.
This study of violent non-state actors is of a truly sweeping order that should be appreciated for its profusion of ideas. The individual authors, all experts in their respective fields, lay out the problems of analysis with the fullest respect for their complexity and state their case with remarkable clarity."" "Christopher Coker, London School of Economics" ""A high quality collection of essays.
Keywords: Non-State Actors (International Relations) -- Political Violence